Carbon Nanotube Yarn for Fiber‐Shaped Electrical Sensors, Actuators, and Energy Storage for Smart Systems. Issue 5 (12th August 2019) - Jang, Yongwoo; Kim, Sung Min; Spinks, Geoffrey M.; Kim, Seon Jeong
Abstract: Smart systems are those that display autonomous or collaborative functionalities, and include the ability to sense multiple inputs, to respond with appropriate operations, and to control a given situation. In certain circumstances, it is also of great interest to retain flexible, stretchable, portable, wearable, and/or implantable attributes in smart electronic systems. Among the promising candidate smart materials, carbon nanotubes (CNTs) exhibit excellent electrical and mechanical properties, and structurally fabricated CNT‐based fibers and yarns with coil and twist further introduce flexible and stretchable properties. A number of notable studies have demonstrated various functions of CNT yarns, including sensors, actuators, and energy storage. In particular, CNT yarns can operate as flexible electronic sensors and electrodes to monitor strain, temperature, ionic concentration, and the concentration of target biomolecules. Moreover, a twisted CNT yarn enables strong torsional actuation, and coiled CNT yarns generate large tensile strokes as an artificial muscle. Furthermore, the reversible actuation of CNT yarns can be used as an energy harvester and, when combined with a CNT supercapacitor, has promoted the next‐generation of energy storage systems. Here, progressive advances of CNT yarns in electrical sensing, actuation, and energy storage are reported, and the future challenges in smart electronic systems considered. Abstract : Carbon nanotubes (CNTs) are currently the most promising material for fiber‐based smart systems. The high mechanical strength and electrical conductivity of CNT yarns have created initial interest in using these materials for smart electronic applications, leading to new types of sensors, actuators, and energy storage devices in integrated smart electronic systems.